Antimicrobial effect of essential oil isolated from Eucalyptus globulus Labill. from Montenegro - Biljana Damjanović-Vratnica; Tatjana Đakov; Danijela Šuković; Jovanka Damjanović (Czech Journal of Food Sciences, 2011)
Chemical composition of the essential oil of Eucalyptus globulus Labill., grown in Montenegro, was analysed by gas chromatography-mass spectrometry and its antimicrobial activity was evaluated against 17 microorganisms, including food poisoning and spoilage bacteria and human pathogens.The Eucalyptus essential oil yield was 1.8% (w/w) on the fresh weight basis, whereas the analysis resulted in the identification of a total of 11 constituents, 1.8 cineole (85.8%), α-pinene (7.2%), and β-myrcene (1.5%) being the main components. Other compounds identified in the oil wereβ-pinene, limonene, α-phellandrene, γ-terpinene, linalool, pinocarveol, terpinen-4-ol, and α-terpineol. The results of the antimicrobial activity tests revealed that the essential oil of E. globulus has rather a strong antimicrobial activity, especially against Streptococcus pyogenes, Escherichia coli, Candida albicans, Staphylococcus aureus, Acinetobacter baumannii, and Klebsiella pneumoniae. Minimum inhibitory concentration revealed the lowest activity against Pseudomonas aeruginosa and Salmonela infantis (3.13 mg/ml) while the highest activity was against S. aureus, E. coli, and S. pyogenes (0.09 mg/ml).